Analisis Yuridis Kewenangan Penyitaan Harta Kekayaan Wajib Pajak oleh Juru Sita Pajak - Julianty Siregar, Riana; Barus, Utary Maharany; Siregar, Taufik (Universitas Medan Area, 2020)
Tax collection in the form of confiscation is a follow-up to the implementation of forced tax collection due to the tax paid not being paid 2x24 hours after the date of notification with the statement and submission of the forced letter to the tax guarantor. The exercise of the authority of the tax bailiff at the East Medan Pratama tax service office is based on tax legislation in the area of taxation, which involves confiscation and hostage taking. In addition, the tax bailiff is also given the authority to enter and inspect all rooms including opening cabinets, drawers and places. others to find confiscated objects at the place of business, at the domicile, or at the place of residence of the tax guarantor, or at other place that can be suspected as a place to store confiscated objects in accordance with the provisions contained in Article 5 paragraph (3) of Law Number 19 of 2000 concerning Tax Collection by Forced Letter.